KEPUASAN NASABAH BCA BERDOMISILI JAKARTA SELATAN TERHADAP KUALITAS LAYANAN M-BANKING - MILLEONA CILENDUAT WARATU (2021)
As one of the largest banks in Indonesia, PT Bank Central Asia (Persero) Tbk. continue to strive to provide the best services and facilities, especially m-banking services so that the customers are increasingly assisted in conducting remote banking activities. Based on this case, a study was conducted to determine the satisfaction of BCA customers with the quality of m-banking services. The author distributes questionnaires to 100 respondents of BCA customers with a focus on customers who are domiciled in South Jakarta. In the questionnaire, there are 26 items based on 7 dimensions of E-SERVQUAL, namely; efficiency, fullfillment, system availability, privacy, responsiveness, compensation, and contact to measure e-service quality. Then Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) methods are used to measure customer satisfaction with the quality of m-banking services. Based on these calculations, the data is then presented into a Cartesian Diagram to provide information on the priority attributes that are considered the most effective to the least effective.